A comparison of flow cytometry, bone marrow biopsy, and bone marrow aspirates in the detection of lymphoid infiltration in B cell disorders. Issue 2 (1st February 2003) - Sah, S P; Matutes, E; Wotherspoon, A C; Morilla, R; Catovsky, D
Abstract : Aims: To evaluate the diagnostic value of bone marrow aspirates, trephine biopsies (BMB), and flow cytometry (FC) in the assessment of bone marrow infiltration in chronic lymphoid disorders. Methods: Investigations were carried out in 110 diagnostic and follow up specimens from B cell disorders, namely: chronic lymphocytic leukaemia (CLL; 65), non-Hodgkin's lymphoma (NHL; 39), and hairy cell leukaemia (HCL; 6). A selected panel of monoclonal antibodies was used both for FC and immunohistochemistry. Results: In CLL there was agreement between the three investigations in 71% of samples and in 88% when only FC and BMB were compared. In nine of 65 samples, FC and BMB were positive, although the aspirate was reported as negative. Four BMB negative samples had minimal residual disease (MRD) detected by FC, whereas two samples were positive both on BMB and aspirate but showed no evidence of disease on FC. In NHL, there was agreement between the three investigations in 22 of 39 cases, and in 27 of 39 cases there was agreement between FC and BMB. In eight of 39 NHL cases, FC was negative but the BMB was either positive (five) or uncertain (three), whereas in three of 39, FC was positive but BMB was either negative (one) or uncertain (two). In three of five uncertain BMB, no clonal population was detected by the polymerase chain reaction, whereas in the remaining two cases the nodular aggregates disappeared on further sectioning. Conclusions: Both BMB and FC are better than bone marrow aspirates for the detection of infiltration in B cell disorders. FC might be slightly more sensitive than BMB to detect MRD in CLL, whereas BMB may be slightly better than FC in NHL.